The Effectiveness of Modern Music Based Physical Fitness Exercise on Students’ Physical Fitness and Motivation in Physical Education - Suharti; Eka Kurnia Darisman; Mulyono; I Gede Dharma Utamayasa (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi FKIP Universitas PGRI Mahadewa Indonesia bekerjasama dengan Asosiasi Prodi Olahraga Perguruan Tinggi PGRI (APOPI), 2026)
This study aims to examine the effectiveness of modern music-based physical fitness exercise on students’ physical fitness and learning motivation in physical education. A quasi-experimental method with a pretest–posttest control group design was employed to compare the outcomes between two groups. The participants consisted of 60 junior high school students, randomly assigned into an experimental group and a control group, each comprising 30 students. The experimental group participated in physical fitness exercises accompanied by modern music (pop and EDM), while the control group followed conventional exercise routines. Physical fitness was measured using the Indonesian Physical Fitness Test (TKJI), covering components such as endurance, strength, speed, and flexibility. Learning motivation was assessed using a validated questionnaire based on self-determination theory. Data analysis was conducted using independent t-tests to determine significant differences between groups. The results revealed that the experimental group demonstrated significantly greater improvements in physical fitness and learning motivation compared to the control group (p < 0,05). The use of modern music enhanced students’ engagement, rhythm coordination, and enthusiasm during exercise sessions, contributing to better overall performance and participation. In conclusion, modern music-based physical fitness exercise is an effective and innovative approach to improving both physical fitness and learning motivation among students. This method provides a more enjoyable and meaningful learning experience and can be recommended as an alternative strategy in physical education teaching practices to promote active participation and better learning outcomes.